2012
DOI: 10.1007/s12282-012-0365-y
|View full text |Cite
|
Sign up to set email alerts
|

Whole breast irradiation for small-sized breasts after conserving surgery: is the field-in-field technique optimal?

Abstract: cFIF has favorable dose conformity and is suggested to be an optimal method for small-sized breasts. However, OT for dose coverage close to the skin and mFIF for normal tissue may also be potential alternatives. Respiratory effects are minimal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Therefore, the difference in lung doses within the used irradiation methods may not have clinical significance. Yang et al (21) compared wedge and FIF IMRT techniques in patients with small-sized breasts. The authors suggested that the conventional FIF method has favorable dose conformity and is an optimal method in patients with breast volume ≤350 cm 3 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the difference in lung doses within the used irradiation methods may not have clinical significance. Yang et al (21) compared wedge and FIF IMRT techniques in patients with small-sized breasts. The authors suggested that the conventional FIF method has favorable dose conformity and is an optimal method in patients with breast volume ≤350 cm 3 .…”
Section: Discussionmentioning
confidence: 99%
“…The authors suggested that the conventional FIF method has favorable dose conformity and is an optimal method in patients with breast volume ≤350 cm 3 . Using the conventional FIF method, the authors reported a lung V20% of 14.42±2.61% and a heart V25% of 2.44±1.07% ( 21 ). Although our patients had a mean breast volume of 493±247 cc using the FIF w/ 2RP method, our results indicated a similar value for the lung V20% of 14±5% and a lower value for the heart V20% of 1.6±1.5%.…”
Section: Discussionmentioning
confidence: 99%
“…As previously mentioned, breast size grouping could be useful in this context, helping to tailor whole breast irradiation. 19 FIGURE 2. Bull's eye diagrams of the left ventricle and segment models of the coronary arteries with reported median D mean distributions in three-dimensional conformal radiotherapy plans, divided in groups according to clinical target volume size.…”
Section: Discussionmentioning
confidence: 99%
“…9,17,18 If a cohort of breast cancer patients with similar breast volume is defined, specific problems and resolutions can be proposed, because breast contours according to breast size and shape may be associated with the variations in the target volume coverage and calculated dose to organs at risk. 19 Three-dimensional treatment planning allows target volume to be measured and CTVs of ≤ 500-975 cm 3 , 975-1.600 cm 3 and ≥ 1.600 cm 3 have been typically, but not consistently, defined as small, medium and large breasts, respectively. 20,21 Additionally, quite a few clinical studies have reported a comparison of the clinical adverse events in regard to the three groups of breast sizes.…”
Section: Introductionmentioning
confidence: 99%